Autophagy in health and disease - Buque Martinez, Aitziber; Galluzzi, Lorenzo (Progress in molecular biology and translational science, 2020)
"Autophagy in Health and Disease, Volume 175, presents the latest insights from renowned experts in the field who discuss the key role of autophagic responses in the preservation of cellular and organismal homeostasis and how defects in the molecular apparatus for autophagy drive or accompany disease. Specific chapters in this new release include Crosstalk between autophagy and cell death signaling: mechanisms and therapeutic relevance, C. elegans to model autophagy-related human disorders, Autophagy in Kidney Disease: advances and therapeutic potential, Autophagy in Chronic Lung Disease, Autophagy in motoneuronal disorders, Strategies employed by viruses to manipulate autophagy, and much more."--Publisher's web page, viewed July 1, 2020